Fabrication and Characterization of K2CeCl5/6LiCl and CeCl3/SrCl2/6LiCl Eutectics for Thermal Neutron Detection - Ryuga Yajima; Kei Kamada; Masao Yoshino; Yui Takizawa; Naoko Kutsuzawa; Rei Sasaki; Takahiko Horiai; Rikito Murakami; Kyoung Jin Kim; Vladimir V. Kochurikhin; Akihiro Yamaji; Shunsuke Kurosawa; et al. (Crystals, 2022)
In recent years, thermal neutron detection using scintillators has been used in a wide range of fields. Thus, the development of scintillators with a higher light yield, faster decay, and higher sensitivity for thermal neutrons is required. In this study, K2CeCl5/6LiCl and CeCl3/SrCl2/6LiCl were developed as novel eutectic scintillators for thermal neutron detection. LiCl was selected as the neutron capture phase and K2CeCl5 and CeCl3 were used as the scintillator phases. The eutectics of K2CeCl5/6LiCl and CeCl3/SrCl2/6LiCl were prepared using the Vertical Bridgman method and the phases were identified by scanning electron microscopy and powder X-ray diffraction measurements. The results of radioluminescence measurements under Ag source X-ray tube irradiation confirmed that the 5d-4f emission derived from Ce3+. The cathodoluminescence spectra and thermal neutron responses of the prepared eutectics were measured to evaluate their optical properties.